2014
DOI: 10.4238/2014.january.24.3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability among the chloroplast genomes of sugarcane (Saccharum spp) and its wild progenitor species Saccharum spontaneum L.

Abstract: ABSTRACT.A striking characteristic of modern sugarcane is that all sugarcane cultivars (Saccharum spp) share a common cytoplasm from S. officinarum. To explore the potential value of S. spontaneum cytoplasm, new Saccharum hybrids with an S. spontaneum cytoplasm were developed at the United States Department of AgricultureAgricultural Research Service, Sugarcane Research Laboratory, through a combination of conventional and molecular breeding approaches. In this study, we analyzed the genetic variability among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Variability in the chloroplast genome had been widely used to investigate phylogenetic relationships and genetic variation among the different species of Saccharum complex (D'Hont et al 1993;Al-Janabi et al 1994;Sobral et al 1994;Takahashi et al 2005;Zhu et al 2014). The present study in chloroplast genetic variation in the Saccharum complex based on cpSSR proved useful in establishing the cytoplasmic variability existing in the Saccharum complex.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in the chloroplast genome had been widely used to investigate phylogenetic relationships and genetic variation among the different species of Saccharum complex (D'Hont et al 1993;Al-Janabi et al 1994;Sobral et al 1994;Takahashi et al 2005;Zhu et al 2014). The present study in chloroplast genetic variation in the Saccharum complex based on cpSSR proved useful in establishing the cytoplasmic variability existing in the Saccharum complex.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplasts (cp) are inherited maternally in most plants, and each of these organelles contains a quadripartite circular molecule of double-stranded DNA that comprises two inverted repeats (IRs), and single-copy regions, the large and small single-copy regions (LSC and SSC). Like most angiosperms, the chloroplasts of sugarcane are inherited maternally [ 6 ]. As a result of their relatively small size, simple structure, and conserved gene content, cpDNA sequences have been widely used for phylogenetic studies, and complete cp genome sequences could provide valuable datasets for resolving taxonomical complexes and/or DNA barcoding (e.g., matK and rbcL ) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the recent advances in molecular markers and genomics-based techniques, the evolutionary aspects of the Saccharum complex and its related genera are beginning to be explored without any ambiguities. Chloroplast DNA, mitochondrial and nuclear ribosomal gene markers were applied to establish the probable polyphyletic origins of Saccharum with sorghum, Erianthus, Miscanthus , and other related genera ( D’Hont et al, 1993 , 1995 ; Selvi et al, 2005 ; Tambarussi et al, 2009 ; Singh et al, 2010 ; Viola et al, 2011 ; Zhu et al, 2014 ; Raj et al, 2016 ). It was found that the closest sugarcane diploid relative that could be identified till date, is Narenga porphyrocoma ( Al-Janabi et al, 1993 ), which had diverged from sugarcane at 2.5 MYA, while S. spontaneum and S. officinarum diverged at 1.5–2 MYA ( Garsmeur et al, 2011 ).…”
Section: Comparative Genomicsmentioning
confidence: 99%